Determining the prevalence of urogenital schistosomiasis based on the discordance between egg counts and haematuria in populations from northern Tanzania - Nordin, Per; Nyale, Edwin; Kalambo, Clement; Ahlberg, Beth Maina; Feldmeier, Hermann; Krantz, Ingela (Frontiers in Tropical Diseases, 2023)
Objectives The presence of schistosomal eggs in the urine is a sufficient but not necessary condition for an individual to be diagnosed with urogenital schistosomiasis. The absence of eggs does not prove that a person is disease-free. Thus, when examining populations using egg occurrence, there is a real risk of underestimating the prevalence. The aim is to develop an easy to use model for improved prevalence estimates of urogenital schistosomiasis. Design and methods Urine samples were taken from 161 schoolchildren and 124 adults on three different days for each individual. The probands were recruited from two areas in northern Tanzania with varying prevalence of urogenital schistosomiasis. The presence of eggs by microscopy and haematuria by dipstick were recorded for each sample and the measurements combined using the discordance of the outcomes. Result As a consequence of applying the developed model, a substantial increase in the prevalence estimate was noted for groups displaying a low egg occurrence. Conclusion By using the biological relationship that exists between the presence of eggs and blood in urine of an infected individual, we provide a way of adjusting the prevalence estimates of urogenital schistosomiasis, using the observed prevalence of haematuria, in the absence of competing causes.